Urgensi Memilih Pasangan Setara (Sekufu’) Studi Terhadap Q.S An-Nur Ayat 26 - Rahmi Mutiara Dalimunthe; Nawir Yuslem (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Qur'an provides comprehensive guidance to enable humanity to live according to established rules and principles, which remain relevant until the end of time. This includes regulations related to marriage, which Islam has outlined broadly in the Qur'an. The concept of marriage in contemporary times demands equality between husband and wife, making this equality an essential consideration when choosing a life partner whether they are balanced, equal, or of the same standing. This concept in Islamic law is referred to as kafa’ah or commonly known as kufu’. It is considered important because kafa’ah fosters harmony and equality in navigating the journey of married life. This study employs a qualitative descriptive analysis method and uses a library research approach, collecting data from literature books and journal articles. The findings indicate that the concept of kafa’ah is a significant aspect recommended in marriage. It serves as a preventive measure or anticipation against potential future issues that may disadvantage the wife. Ideally, women should play a central role in determining kafa’ah criteria beyond religion. This is essential to achieve welfare and to support the progressive development of Muslim women.